Organic Semiconductor Lasers: Lasing Operation under Long‐Pulse Excitation in Solution‐Processed Organic Gain Medium: Toward CW Lasing in Organic Semiconductors (Advanced Optical Materials 21/2020). Issue 21 (4th November 2020) - Mai, Van T. N.; Shukla, Atul; Senevirathne, A. M. Chathuranganie; Allison, Ilene; Lim, Hyunsoo; Lepage, Romain J.; McGregor, Sarah K. M.; Wood, Michael; Matsushima, Toshinori; Moore, Evan G.; Krenske, Elizabeth H.; Sandanayaka, Atula S. D.; et al.
Abstract : Accumulation of triplets under long‐pulse photoexcitation has been the key obstacle to the achievement of long‐pulse lasing activity for organic semiconductor laser dyes. Chihaya Adachi, Ebinazar B. Namdas, Shih‐Chun Lo and co‐workers (article number 2001234 ) demonstrate the first lasing action under long‐pulse optical excitation from a novel solution processable organic semiconductor laser dye. The negligible spectral overlap between triplet excited‐state absorption and photoluminescence emission, together with high radiative decay rate and high photoluminescence quantum yield, empowers the long‐pulse lasing activity.